Biomimetic hydrogel blanket for conserving and recovering intrinsic cell properties - Um, Seung-Hoon; Seo, Youngmin; Seo, Hyunseon; Lee, Kyungwoo; Park, Sun Hwa; Jeon, Jung Ho; Lim, Jung Yeon; Ok, Myoung-Ryul; Kim, Yu-Chan; Kim, Hyunjung; Cheon, Cheol-Hong; Han, Hyung-Seop; et al. (The Korean Society for Biomaterials | BioMed Central, 2022)
BackgroundCells in the human body experience different growth environments and conditions, such as compressive pressure and oxygen concentrations, depending on the type and location of the tissue. Thus, a culture device that emulates the environment inside the body is required to study cells outside the body. MethodsA blanket-type cell culture device (Direct Contact Pressing: DCP) was fabricated with an alginate-based hydrogel. Changes in cell morphology due to DCP pressure were observed using a phase contrast microscope. The changes in the oxygen permeability and pressure according to the hydrogel concentration of DCP were analyzed. To compare the effects of DCP with normal or artificial hypoxic cultures, cells were divided based on the culture technique: normal culture, DCP culture device, and artificial hypoxic environment. Changes in phenotype, genes, and glycosaminoglycan amounts according to each environment were evaluated. Based on this, the mechanism of each culture environment on the intrinsic properties of conserving chondrocytes was suggested. ResultsChondrocytes live under pressure from the surrounding collagen tissue and experience a hypoxic environment because collagen inhibits oxygen permeability. By culturing the chondrocytes in a DCP environment, the capability of DCP to produce a low-oxygen and physical pressure environment was verified. When human primary chondrocytes, which require pressure and a low-oxygen environment during culture to maintain their innate properties, were cultured using the hydrogel blanket, the original shapes and properties of the chondrocytes were maintained. The intrinsic properties could be recovered even in aged cells that had lost their original cell properties. ConclusionsA DCP culture method using a biomimetic hydrogel blanket provides cells with an adjustable physical pressure and a low-oxygen environment. Through this technique, we could maintain the original cellular phenotypes and intrinsic properties of human primary chondrocytes. The results of this study can be applied to other cells that require special pressure and oxygen concentration control to maintain their intrinsic properties. Additionally, this technique has the potential to be applied to the re-differentiation of cells that have lost their original properties.